Selecting Effective Influence Principles for Tailoring Gamification-Based Strategies to Player Roles - Borges, Simone S.; Durelli, Vinicius H. S.; Reis, Helena M.; Bittencourt, Ig. I.; Mizoguchi, Riichiro; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2017)
Gamification is a term that refers to the use of game elements in non-game contexts with the goal of engaging people in a variety of tasks. Gamification can be an effective persuasive tool for motivating learners and lately we have witnessed a growing interest in gamified learning systems. However, the efforts of the research community in the last years have shown the weakness of one-size-fits-all and design-by-intuition approaches. Thus, there is room for improvement. Persuasion profiling is a promising technique to fill such a gap. This paper discusses how gamification design can benefit from persuasion profiling. To measure users’ susceptibility to influence principles, we employed the Br-STPS. We conducted a study on 149 subjects which examined the persuasiveness of six influence principles on five player types. The results suggest that player types indeed has a role to play in term of the perceive persuasiveness of users. Moreover, we present a list of persuasive strategies and how they can either enhance or halt user’s motivation. Thus, evidence suggest that gamification design could benefit of influence principles, although tailored solutions are necessary to minimize the risks of selecting counter-tailored and ill-defined persuasive strategies.